1993
DOI: 10.1093/carcin/14.10.2019
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of mammary epithelial cell proliferation in pituitary isografted BALB/c mice

Abstract: Recently, we have published that treatment of pituitary isografted BALB/c mice with a single injection of N-methyl-N-nitrosourea (MNU) leads to the rapid development of mammary tumors in over 90% of the animals (Guzman et al., Cancer Res., 52, 5732-5737). In the present study, we characterized the changes in proliferative activity and lobulo-alveolar differentiation of MECs at different time intervals after isografting animals with pituitary glands. Virgin BALB/c mice 1, 3, 5 or 8 weeks after pituitary isograf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 0 publications
1
22
0
Order By: Relevance
“…Control animals, in which only senescent cells were injected, did not develop palpable tumours through the course of these experiments. Mice were injected with 70 mg kg À1 body weight BrdU 2 h prior to tumour harvest to measure proliferation in sorted GFP ( þ ) tumour cells (Christov et al, 1993). Cells from DU145 tumours established with or without senescent cells and collected after 5 weeks contain similar fractions of proliferating cells as measured by BrdU uptake and DNA profiling (data not shown).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Control animals, in which only senescent cells were injected, did not develop palpable tumours through the course of these experiments. Mice were injected with 70 mg kg À1 body weight BrdU 2 h prior to tumour harvest to measure proliferation in sorted GFP ( þ ) tumour cells (Christov et al, 1993). Cells from DU145 tumours established with or without senescent cells and collected after 5 weeks contain similar fractions of proliferating cells as measured by BrdU uptake and DNA profiling (data not shown).…”
Section: Resultsmentioning
confidence: 98%
“…Tumour dimensions were measured at 3, 4 and 5 weeks after injection using a caliper. BrdU was injected into these mice interperitoneally at a concentration of 70 mg kg À1 body weight (Christov et al, 1993), harvested 2 h later and dissociated into a single-cell suspension from which GFP ( þ ) cells were isolated by fluorescence-activated cell sorting. These were fixed in ice-cold ethanol and stored at À201C.…”
Section: Xenograft Coculturesmentioning
confidence: 99%
“…Christov et al (1993) have shown that maximal mammary proliferation (7.7 ± 10.7%) occurs at approximately three weeks post-isograft and decreases back to the baseline after 5 ± 8 weeks. If the Bcl-2 transgene is exerting an antiproliferative e ect in the transgenic mammary glands, the maximal di erence in proliferation between that and the nontransgenic gland would theoretically be seen at almost exactly the same time as the carcinogen treatments, which were performed at weeks 2 and 3 post-isograft.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with DMBA is known to cause adduct formation in genomic DNA which, if improperly repaired, would result in mutations (Ross and Nesnow, 1999). In contrast, pituitary isografts provide a mitogenic stimulus similar to that encountered during midpregnancy (Christov et al, 1993), and therefore, is thought to act to expand a population of cells bearing initiating mutations. Given the role of p53 in recognizing and ensuring DNA repair, the eect attributable to DMBA was surprisingly small.…”
Section: Discussionmentioning
confidence: 99%